A proposal on BRAC bank project 1990-93 - BRAC (© BRAC, 2016)
1.BRAC bank project proposal 2. Loan proposal 3. Major scheme 4. Money transfer procedure 5. Savings 6. Structure and management 7. Accounts 8. RDP statistical summary .